2022
DOI: 10.1088/1748-605x/ac5ffe
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of Ti3C2-MXene-incorporated composite scaffolds for accelerated bone regeneration

Abstract: Grafting of bone-substitute biomaterials plays a vital role in the reconstruction of bone defects. However, the design of bioscaffolds with osteoinductive agents and biomimetic structures for regeneration of critical-sized bone defects is difficult. Ti3C2 MXene—belonging to a new class of two-dimensional (2D) nanomaterials—exhibits excellent biocompatibility, and antibacterial properties, and promotes osteogenesis. However, its application in preparing 3D-printed tissue-engineered bone scaffolds for repairing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 64 publications
0
37
0
Order By: Relevance
“…[25] Different techniques have also been employed to process the MXene-based nanocomposites into various shapes and architectures, such as membrane, nanofiber, porous material, polymeric microparticles, and 3D-printed products (Figure 1). [26][27][28]…”
Section: Mxene-integrated Nanocompositesmentioning
confidence: 99%
See 3 more Smart Citations
“…[25] Different techniques have also been employed to process the MXene-based nanocomposites into various shapes and architectures, such as membrane, nanofiber, porous material, polymeric microparticles, and 3D-printed products (Figure 1). [26][27][28]…”
Section: Mxene-integrated Nanocompositesmentioning
confidence: 99%
“…Reproduced under terms of the CC-BY license. [27] Copyright 2022, The Authors, published by IOP Publishing. quality of wound healing and skin regeneration has been a challenge for those wounds infected with bacteria, particularly drug-resistance bacteria.…”
Section: Infection Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Their study suggested that MXene composite scaffolds exhibit osteoinductivity and can fulfill the requirements of regeneration of critical-sized bone defects. 211 In another study by Chen et al, strong biocompatible Ti 3 C 2 T z -based MXenes nanosheets were applied on poly (lactic acid) (PLA) membranes and the histological studies revealed enhanced cell adhesion, proliferation, and osteogenic differentiation. 212 There also has been report of using 0D titanium carbide (Ti 3 C 2 ) MXene quantum dots (MQDs) along with BMMSC within chitosan-based hydrogel to create a 3D platform for enhancing material-based tissue repair after injury.…”
Section: Mxenes Nanomaterialsmentioning
confidence: 99%